Qualitative Study the Correlation between Intensity of Reciting the Quran with Students Anxiety in facing Objective Structured Clinical Examination (OSCE) on Medical Licensing Examination Uji Kompetensi Mahasiswa Program Profesi Dokter (UKMPPD) - Syayma Karimah; Ratna Kusumawati; Bulan Kakanita Hermasari (Nexus Pendidikan Kedokteran dan Kesehatan, 2016)
Introduction: Objective Sturctured Clinical Examination (OSCE) on medical licensing examination Uji Kompetensi Mahasiswa Program Profesi Dokter (UKMPPD) that determines students to become a medical doctor is high potentially causing anxiety. There are some methods to overcome someone anxiety, one of them is by doing spiritual activity like reciting the Quran. The purpose of this study was to explore the correlation between intensity of reciting the Quran with students anxiety in facing OSCE on medical licensing examination. Methods: The research design was a qualitative study with phenomenology approach.The sampling technique was purposive sampling method. The sample was medical students of Faculty of Medicine University of Sebelas Maret Surakarta those were participating OSCE medical licensing examination on November 2015. The informations obtained by focus group interview to eight students. Analysis of the data in this study was done by content analysis method. Results: This study showed the reasons of students anxiety, manifestations of students anxiety, and the methods those were used by sudents to decrese their anxiety in facing OSCE medical licensing examination. The correlation between doing spiritual activities especially intensity of reciting the Quran with students anxiety in facing examinations also found in this study. Conclusion: This study concludes doing spiritual activities especially reciting the Quran decreases students anxiety in facing examination. Keywords: anxiety, intensity of reciting the Quran, Obejective Structured Clinical Examination, medical licensing examination, Uji Kompetensi Mahasiswa Program Profesi Dokter (UKMPPD)